Effectiveness of Dual Situated Learning Model in Improving High School Students’ Conceptions of Chemistry Equilibrium and Preventing Their misconceptions - Muhammad Ali Kurniawan; Sri Rahayu; Fauziatul Fajaroh; Saeed Almuntasheri (Universitas Pendidikan Indonesia, 2020)
This study aims to compare the impact of the Dual Situated Learning Model (DSLM) and conventional instructions in improving High School Students’ understanding of chemical equilibrium concepts and the prevention of possible misconceptions. The study utilized a quasi-pretest-posttest control and experimental group design with two classes of XI SMAN as the research sample (N=60 students). Pre-posttests consisting of 12 two-tier questions (r = 0.691) used to assess the learners’ understanding of the chemical equilibrium. The results showed a significant difference in favor of the learners who taught using the DSLM model in comparison to those in the conventional approaches (Fount = 4.149; p = 0.003). Students in the experimental class had a better understanding and fewer misconceptions about the concept of chemical equilibrium. Implications for science educators suggest that learning that is designed by considering students' misconceptions or preconceptions and anticipating them through appropriate learning steps will have a positive influence on the learners’ conceptual understanding.